2007
DOI: 10.1590/s1415-47572007000400024
|View full text |Cite
|
Sign up to set email alerts
|

CUG-BP and 3'UTR sequences influence PARN-mediated deadenylation in mammalian cell extracts

Abstract: Several mRNAs have been shown to exhibit distinct patterns of poly(A) shortening prior to their decay in vivo. In this study, we show that individual transcripts also demonstrate distinct patterns of deadenylation in in vitro systems derived from HeLa and Jurkat T cell cytoplasmic extracts. The major patterns observed were slow/synchronous and fast/asynchronous poly(A) tail shortening. For all RNA substrates tested, PARN was shown to be the enzyme responsible for the deadenylation patterns that were observed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 57 publications
(61 reference statements)
0
3
0
Order By: Relevance
“…Structures derived from Raver1 peptide-RRM complexes reveal the versatility of RRMs as a recognition motif in mediating protein interactions across the distal helical face while engaged in RNA binding across the β-sheet. By analogy, recent studies using in vitro assays for assessing mRNA decay in AU-rich mRNAs have shown that CELF1 binds specifically to mRNAs and stimulates poly(A) shortening in the 3′ UTR by recruiting the poly(A) deadenylase PARN (13,30). Although the details of this interaction are still ill-defined, it would appear that a Ser-rich motif within the RRM2-RRM3 flexible linker region of CELF1, close to a putative amphipathic helical motif (residues 332–340), facilitates recruitment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Structures derived from Raver1 peptide-RRM complexes reveal the versatility of RRMs as a recognition motif in mediating protein interactions across the distal helical face while engaged in RNA binding across the β-sheet. By analogy, recent studies using in vitro assays for assessing mRNA decay in AU-rich mRNAs have shown that CELF1 binds specifically to mRNAs and stimulates poly(A) shortening in the 3′ UTR by recruiting the poly(A) deadenylase PARN (13,30). Although the details of this interaction are still ill-defined, it would appear that a Ser-rich motif within the RRM2-RRM3 flexible linker region of CELF1, close to a putative amphipathic helical motif (residues 332–340), facilitates recruitment.…”
Section: Discussionmentioning
confidence: 99%
“…In Xenopus , CELF1 induces deadenylation and appears to play a key role in regulating poly(A) shortening (27–29). Recent studies, using in vitro assays for assessing mRNA decay in AU-rich mRNAs, have shown that CELF1 binds specifically to mRNAs and stimulates poly(A) shortening in the 3′ untranslated region (3′ UTR) by recruiting the poly(A) deadenylase ribonuclease (PARN) (13,30). In this case, binding to target EDEN mRNA GU-rich elements (GREs) is necessary for function (2,12,31–35), with EDEN-dependent deadenylation regulated by neighbouring cis -acting AU-rich elements (AREs) (13).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation